Ruptures’ Weight. Access to ICT by rural teachers and school path - Carniglia, Edgardo (2015)
A situated perspective of access to ambivalent ICT (Information and Communication Technologies) in the country indicates that any digital transition involves significant breaks of everyday experience. This text analyzes the appropriation of digital devices by rural teachers that installs a certain historical trajectory of the school as an intervener status in the digitization of education. These appropriations represent tense interpenetrations between individual attributes and contextual conditions of access to computers, mobile phones and networks in a techno-cultural environment with increasing acceptance of ICT. The fieldwork identifies historical features of the rural school and brands of the institutional trajectory significant for teachers who appropriate ICT in the classroom and the school. The analyzed testimonies correspond to semi-structured interviews with teachers in public elementary schools from adepartment of the province of Córdoba (Argentina) with extensive and commercial agriculture.